Dialektika Hak Ijbar dalam Undang-Undang Perkawinan Perspektif Fiqh Sosial MA. Sahal Mahfudh - Muh. Luthfi Hakim (Program Studi Hukum Keluarga Islam, 2022)
Ijbar rights provisions in the Marriage Law have not been able to have a significant impact on efforts to prevent cases of forced marriages from occurring. There are still many cases of abuse of forced marriage practices committed by parents against their children under the pretext of religion (Islam). This article aims to examine the concept of ijbar rights in the Marriage Law using the concept of Social Fiqh MA. Sahal Mahfudh. The type of method used in writing this article is normative juridical with a conceptual approach and statutory regulations. Data collection techniques are in the form of documentation by searching for data in the form of books, research results, and other literature related to the issue of ijbar rights in marriage. The results of the study show that in the concept of Social Fiqh the provisions on ijbar rights in the Marriage Law have relevance to current conditions and can be a solution to the misunderstanding of the majority of mujbir wali in interpreting the concept of ijbar rights. The concept of social Fiqh also views that the right of ijbar in the Marriage Law can prevent disputes between the mujbir wali and someone who is under his guardianship. Disputes between guardians and their daughters can be resolved by compromising the authority of the mujbir guardian and the rights of the child which also needs to be considered proportionally.Ketentuan hak ijbar dalam Undang-Undang Perkawinan masih belum mampu memberikan dampak signifikan dalam upaya mencegah terjadinya kasus perkawinan paksa. Masih banyak dijumpai penyalahgunaan praktik-praktik kawin paksa yang dilakukan oleh orangtua terhadap anaknya dengan dalih agama (Islam). Artikel ini bertujuan untuk menelaah konsep hak ijbar dalam Undang-Undang Perkawinan dengan menggunakan konsep Fiqh Sosial MA. Sahal Mahfudh. Jenis metode yang digunakan dalam penulisan artikel ini adalah yuridis normatif dengan pendekatan konseptuan dan peraturan perundang-undangan. Teknik pengumpulan data berupa dokumentasi dengan cara mencari data-data berupa buku, hasil penelitian, dan literatur lainnya yang berkaitan permasalahan hak ijbar dalam perkawinan. Hasil penelitian menunjukkan bahwa dalam konsepsi Fiqh Sosial ketentuan hak ijbar dalam Undang-Undang Perkawinan memiliki relevansi dengan kondisi saat ini dan mampu menjadi solusi atas kesalahan pemahaman mayoritas wali mujbir dalam memaknai konsep hak ijbar. Konsep Fiqh sosial juga memandang bahwa hak ijbar dalam Undang-Undang Perkawinan dapat mencegah terjadinya perselisihan antara wali mujbir dengan seseorang yang berada di bawah perwaliannya. Perselisihan antara wali dengan anak perempuannya dapat diselesaikan dengan cara mengkompromikan antara kewenangan wali mujbir dengan hak anak yang juga perlu diperhatikan secara proporsional.